Pulmonary function after bone marrow transplantation for chronic myeloid leukaemia. Issue 3 (March 1988) - Sutedja, T G; Apperley, J F; Hughes, J M; Aber, V R; Kennedy, H G; Nunn, P; Jones, L; Hopper, L; Goldman, J M
Abstract : Pulmonary function was measured before and at intervals after treatment in 44 patients who received a bone marrow transplant for chronic myeloid leukaemia in the chronic phase. All patients were treated with cytotoxic drugs, total body irradiation, and post-graft immunosuppression. Thirty four patients surviving for 12 months were followed at three monthly intervals and 16 patients for 24 months. Fifteen patients received unmanipulated donor marrow cells and 29 patients received donor marrow cells depleted of lymphocytes ex vivo with the monoclonal antibody Campath-1. The 21 patients treated early in this study received 10 Gy of total body irradiation whereas the 23 patients treated more recently, who were all T lymphocyte depleted, received 12 Gy. Pretransplant lung function for the group was normal and was similar in survivors (n = 34) and nonsurvivors (n = 10), and in smokers (n = 8) and non-smokers (n = 36). (Carbon monoxide transfer factor--TLCO) was under 75% of predicted normal in nine patients before transplantation. TLCO, carbon monoxide transfer coefficient (KCO), FEV1, and vital capacity (VC) values were lower 6 and 12 months after bone marrow transplant than initially. The greatest decline was in TLCO, from an initial value of 89% to 66% at 6 and 70% at 12 months. The 16 longer term survivors showed significant recovery of function between 6 and 24 months after bone marrow transplant for TLCO, KCO, and VC, the increase ranging from 6.3% to 7.3% predicted. Airflow obstruction (FEV1/VC ratio less than 70%) developed in one patient. The major factors associated with deterioration in pulmonary function at 6 and 12 months after transplantation in the 34 survivors (stepwise multiple regression analysis) were (a) transplantation with T cell depleted donor marrow (p less than 0.005) and higher total body irradiation dose (p less than 0.02) with a fall in KCO and an increase in the FEV1/VC ratio; (b) chronic graft versus host disease with a fall in VC (p less than 0.01); and less fall in KCO (p less than 0.01); and (c) acute graft versus host disease with a fall in FEV1 (p less than 0.01). It is considered that most patients who survive the short term risks of bone marrow transplant have only minor long term impairment of pulmonary function.